2019
DOI: 10.7150/ijms.33106
|View full text |Cite
|
Sign up to set email alerts
|

The extracts of Astragalus membranaceus enhance chemosensitivity and reduce tumor indoleamine 2, 3-dioxygenase expression

Abstract: Astragalus membranaceus has been shown to possess anti-inflammation and antitumor properties. Several studies have indicated that extracts of Astragalus membranaceus (PG2) have growth inhibitory effects on tumor. However, the effect of PG2 on enhancing the chemotherapy, modulating tumor immune escape and their mechanism of action is unknown and need further investigation. Connexin (Cx) 43 is ubiquitous in cells and involved in facilitating the passage of chemotherapeutic drugs to bystander tumor cells. The ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Dr. Sheu and his colleagues, the experts in the field, found that hinokitiol inhibits tumor cell migration via blocking the phosphorylation of mitogen-activated protein kinase and p65 nuclear factor kappa B (NF-κB) [15]. Our findings verified that the expression of phosphorylated Akt/Erk is decreased in hinokitiol-treated B16F10 and 4T1 tumor cells, which is consistent with the results published by other groups [15][16][17][18][19]. We also used resveratrol and constitutively active Akt transfection to make a thorough inquiry on the association of heparanase and these two pathways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dr. Sheu and his colleagues, the experts in the field, found that hinokitiol inhibits tumor cell migration via blocking the phosphorylation of mitogen-activated protein kinase and p65 nuclear factor kappa B (NF-κB) [15]. Our findings verified that the expression of phosphorylated Akt/Erk is decreased in hinokitiol-treated B16F10 and 4T1 tumor cells, which is consistent with the results published by other groups [15][16][17][18][19]. We also used resveratrol and constitutively active Akt transfection to make a thorough inquiry on the association of heparanase and these two pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Murine melanoma cells (B16F10) [16] and murine mammary carcinoma (4T1) cells [17] were maintained in 10cm culture dish with Dulbecco's Modified Eagle Medium (DMEM) containing 1% Penicillin-Streptomycin (100 units/mL penicillin and 100 μg/mL streptomycin), and 10% fetal bovine serum (FBS). Both B16F10 and 4T1 cells were incubated at 37°C, 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…Astragalus membranaceus (AM) is a traditional Chinese medicine widely used in clinical therapy and health care. It has been reported to exert a wide range of biological activities, such as enhanced immune functions [ 24 ], strengthened cardiac functions [ 25 ], antidiabetic properties [ 26 ], and antitumor [ 27 ], antiviral [ 28 ], antioxidant [ 29 , 30 ], and longevity effects [ 31 ]. In recent years, several studies have found that AM exhibits also anti-inflammatory effects by regulating the secretion of inflammatory factors [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus polysaccharide is the main active component in the dried root extract of Astragalus membranaceus, and it has been shown that Astragalus polysaccharide has pharmacological effects of regulating inflammatory cascade, antitumor [19], and immune modulation [20], and recent experimental results have confirmed that Astragalus polysaccharide can inhibit the proliferation and metastasis of tumor cells through various mechanisms. APS, as one of the main active components of Astragalus, has important pharmacological effects such as anti-tumor and immune modulation [21].…”
Section: Tumor Markersmentioning
confidence: 99%